PENGARUH LATIHAN TARGET TERHADAP PENINGKATAN AKURASI SHOOTING PEMAIN FUTSAL - Rizky Roberto Simbolon, - (2023)
The purpose of this research is to find out how much the effect of target practice has on increasing shooting accuracy in futsal players. The type of research used in this study was quasi-experimental with a research design using a Pretest-Posttest Control Group Design. In this study there were two groups: the Experimental Group and the Control Group. The experimental group was given target training treatment while the control group was not given conventional treatment or training. The treatment was given 12 meetings in one month. Sampling in this study using saturated sampling technique. With a total sample of 20 people, the sample was divided into 2 groups using the A-B-B-A technique according to the ranking of the initial test. The test instrument in this study was a shooting test using targets. Data analysis used the t test (paired sample t test) at the 0.05 level. From the results of the study it was found that there was a significant effect on the experimental group that had received target practice treatment on shooting accuracy, compared to the control group that was not given conventional treatment or training. This can be seen from the value of ρ = 0.000 <0.05 indicating that there is an effect of target training on increasing the shooting accuracy of futsal players. While the control group has a value of ρ = 0.014 > 0.05 indicating that there is no significant effect of conventional training on increasing accuracy in futsal players. The conclusion of this study is that target practice has a significant effect on increasing shooting accuracy.